Influence of Polymeric Blends on Bioceramics of Hydroxyapatite - Eduardo da Silva Gomes; Antônia Millena de Oliveira Lima; Sílvia Rodrigues Gavinho; Manuel Pedro Fernandes Graça; Susana Devesa; Ana Angélica Mathias Macêdo (Crystals, 2023)
Bioceramics are used to repair, rebuild, and replace parts of the human body, e.g., bones, joints and teeth, in the form of powder, coatings or prostheses. The synthetic hydroxyapatite [Ca10(PO4)6(OH)2 (HAP)] based on calcium phosphate has been widely used in the medical and dental areas due to the chemical similarity with the inorganic component of human bone tissue. In this work, hydroxyapatite nanocrystalline powders were synthesized by the solid-state reaction method and sintered with a galactomannan and chitosan blend. The bioceramics studied were prepared from 70%, 80% and 90% of hydroxyapatite with 30%, 20% and 10% of galactomannan and chitosan blends, respectively. The influence of the blend content on the bioceramics was investigated through structural, vibrational, thermal, morphological and dielectric characterizations. It was observed that the increase in the blend percentage promoted an increase in the grain size, which was followed by a decrease in the density and hardness of the samples. The sample with a higher amount of polymeric blend also presented a higher dielectric constant and higher losses.